Analysis of the Influence of Leadership and Organizational Climate on Motivation and Employee Performance - Muhammad Reza Pahlevi; Syamsu Alam; Maat Pono (Magister Management, Hasanuddin University, 2022)
The purpose of this study was to analyze the influence of leadership, organizational climate on motivation and employee performance at PT Indonesia Port Corporation IV in Makassar Area. The study applied samples of 86 employees out of 615 population. Data collection methods using questionnaires and then analyzed using path analysis. The research model confirms the existing literature that leadership and organizational climate have a significant and positive effect on motivation. The results also showed that leadership, organizational climate, and employee motivation have a significant and positive effect on employee performance. research also shows the positive and significant result on the influence between leadership on employee performance through employee motivation. It is also the same for organizational climates to impact employee performance through employee motivation.